Dublin City University, 1980-2020 designed to be different - Kinsella, Eoin ca. 20./21. Jh (Four Courts Press, 2020)
Dublin City University has grown rapidly from its origins as the National Institute for Higher Education, Dublin, which admitted just 200 students when it first opened in 1980. NIHED emerged from a fundamental review of the third level sector during the 1960s and 1970s. The path to university status in 1989 was not smooth, requiring strong leadership, vision and significant philanthropic support during a time of economic crisis. DCU is one of Ireland?s youngest universities, and over the past four decades has become one of the most successful young universities in the world. It has been widely recognized as an innovative institution, strongly engaged in local, national and international communities and networks. Today the university has more than 17,000 students across three campuses in the north of the city, integrating four formerly independent colleges. This book relates the major achievements and many challenges in the forty years of DCU?s growth, examining key policy and strategy decisions, the contributions of leading personalities, and the collective experiences of staff and students